Adjuvanted subunit intranasal vaccine reduces SARS-CoV-2 onward transmission in hamsters - Sui, Yongjun; Kar, Swagata; Chawla, Bhavna; Hoang, Tanya; Yu, YuanKai; Wallace, Shannon M.; Andersen, Hanne; Berzofsky, Jay A. (Frontiers in Immunology, 2025)
IntroductionMost COVID-19 vaccine trials have focused on recipient protection, not protection of their contacts, a critical need. As a subunit intranasal COVID-19 vaccine reduced nasopharyngeal virus more than did an intramuscular (IM) vaccine, we hypothesized that this vaccine might reduce onward transmission to others.MethodsWe vaccinated hamsters with either the IM-administrated licensed mRNA vaccine twice or one dose of mRNA IM followed by adjuvanted subunit intranasal vaccine. 24 hours after SARS-CoV-2 challenge, these animals were housed with naïve recipients in a contactless chamber that allows airborne transmission.ResultsOnward airborne transmission was profoundly blocked: the donor and recipients of the intranasal vaccine-boosted group had lower oral and lung viral loads (VL), which correlated with mucosal ACE2 inhibition activity. Notably, in this head-to-head comparison of COVID-19 booster vaccines on SARS-CoV-2 onward transmission, we found that statistically significant viral reduction in the lung tissues and oral swabs was observed only in the intranasal S1 nanoparticle vaccine-boosted group, but not in the systemic mRNA vaccine-boosted group, suggesting the superior protection of this intranasal vaccine, which could act as an attractive vaccine booster candidate to complement the current licensed systemic vaccines.DiscussionOverall, our study strongly supports the use of the intranasal vaccine as a boost to protect not only the vaccinated person, but also people exposed to the vaccinated person, a key public health goal.